The Result of Acute Maternal Morbidity and Management at A Tertiary Care Hospital's Critical Care Unit: A Cross-Sectional Study - Shehreen Memon, Sanam Channa, Nadia Hameed, Yasmeen Bibi, Muhammad Nadeem Chohan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the results of the management of severe acute maternal conditions in a public hospital's critical care unit. Study design: A cross-sectional study Place and Duration: From 19-09-2018 to 18-03-2019, the ICU and Department of Obstetrics and Gynecology at Liaquat University Hospital in Hyderabad Methodology: This study comprised 50 women who needed admission to an ICU and care during pregnancy and/or puerperium for up to 6 weeks. The information was entered into a pre-designed proforma with factors including complete biodata and a detailed history. Clinical findings, overall health, length of hospital stay, treatment results, and problems Results: The women were 29 years old on average in 18 to 45. 63 years. Pre-eclampsia affected 16% of women (n = 8) and eclampsia affected 38% of women (n = 19). Similar obstetric bleeding conditions were seen, including postpartum haemorrhage (24%; n=12), abruptio placenta (2%), placenta previa (8%), ectopic pregnancy (2%), and abortion (2%). Dystocia-related conditions included 4% (n=2) prolonged or obstructed labours, 2% (n=1) uterine ruptures, and 2% (n=1) cases in which an approaching rupture was noted. The findings indicated that women who need to be admitted to be cared for in an ICU throughout pregnancy and puerperium experience multiple complications. The most frequent reasons for admission to the intensive care unit were respiratory failure, hemodynamic instability, and neurologic dysfunctions. The majority of the women who were admitted to the ICU in shock and required emergency care were kept on a ventilator. Five women experienced difficulties during their 9.8+18.8 day average stay in the ICU. Deaths were noted in 54% (n=27) of the cases, with 40% (n=20) receiving discharges and 6% (n=3) being referred to another hospital. Practical Implication: Cases of severe maternal morbidity warrant quality evaluation, much like cases of maternal fatality. Institutions and systems should either use an existing screening criterion or develop their own list of outcomes that warrant evaluation in the absence of agreement on a comprehensive list of disorders that reflect severe maternal morbidity. Conclusion: PPH (Eclampsia and Preeclampsia) and the hypertensive condition of pregnancy were significant contributors to maternal illness in this study. Carefully securing the mother's adaption, particularly in distant places, will lessen the issues that necessitate the transfer to the ICU. Obstetrician intensivists and anesthetists can further reduce maternal morbidity and mortality in these circumstances. The obstetrics department of the high-dependency unit also helps to decrease mortality. Keywords: Women, preeclampsia, post-partum hemorrhage, morbidity, mortality, intensive care unit